A Framework for Analyzing Absorptive Capacity Using Social Network Analysis (Case Study: Sharif University Innovation Ecosystem) - Mahdi Mohammadi; Mahdi Elyasi; Azadeh Savehshemshaki (مدیریت صنعتی)
Objective Due to the importance of innovation ecosystems in the global economic circle, the absorptive capacity concept is important in Iran, too. Sharif University of Technology is important in establishing innovation clusters, because of its scientific status, access to knowledge resources, and being close to various industries and factories. It also provides a platform for the flow of knowledge between academic and business fields.